The Correlation Between Indoor Air Pollution with the Incident of Toddler’s Pneumonia - Ni Nyoman Dayu Mahalastri (Jurnal Berkala Epidemiologi, 2014)
Pneumonia is a serious health problem in the world, including in Indonesia. Based on the results of Indonesia Basic Health Research (Riskesdas) in 2007, pneumonia was ranked second in the proportion of causes of death in children aged 1-4 years and was below diarrhea which ranks first. Environmental factors or home conditions, especially air quality in the home is said to be one of the factors that can trigger pneumonia in infants. This study was conducted to determine the relationship between air quality factors in the home with toddler pneumonia. This type of research is observational analytic and uses a case-control research design. The case population was all children under five who were visitors to the Public health center (PHC) of Mojo from January 2014 to March 2014 and were diagnosed with pneumonia. Whereas the control population was all children under five who visited the PHC of Mojo from January 2014 to March 2014 and were diagnosed with a disease other than pneumonia. The number of respondents in this study was 60 respondents. Sample selection with simple random sampling. The variables studied were exposed to cigarette smoke in the house, ventilation area, and occupancy density. The results of the analysis using Statcalc on the Epi-Info program showed that exposure to cigarette smoke in the home (OR = 4.00), ventilation area (OR = 4.03), and occupancy density (OR = 4.38) have a relationship with the incidence of pneumonia toddler. It is hoped that the community can avoid air pollution in the home in order to prevent toddlers from pneumonia.